IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK DI KABUPATEN SIGI - Kadoy, Arif Ainul (Katalogis, 2018)
The Purpose of this Study were to Describe and analyze the Implementation of Public Disclosure Policy in Sigi Regency. This study was a ualitative research using descriptive analysis, i.e. to describe a variety conditions, situations, phenomena, and realities of a research object. Inthis study, the researcher would collect data to draw the realities of the implementation of Public Disclosure Policy in Sigi Regency as well as to describe the factors supporting and inhibiting the implementation process. Data collection techniques used were interviews, observation, and documentary study. Based on the analysis of the research results, it could be concluded that the Implementation of Public Disclosure Policy in Sigi Regency had not been maximized. From the Grindle’s nine indicators influencing policy implementation, there were still four variables that had not been implemented, while the other fife variables had been implemented. On the variable o policy contents, from the six indicators, there were still three variables that had not been implemented, namely (1) target group interest; (2) benefit types; and (3) decision making location. While the three other indicators that had been implemented were (1) desired change degree; (2) program implementation; and (3) resource involved. Furthermore, in the variable of policy contents consisting of three indicators, there was still one indicator that had not been implemented, namely the power, interests, and strategies of the actors involved. Meanwhile, two other indicators had been implemented, namely (1) institutions and authorities characteristics; and (2) compliance and responsiveness.